PELATIHAN PENGEMBANGAN APLIKASI GAME DENGAN SCRATCH DI SMK NEGERI TEMBARAK TEMANGGUNG - Muhammad Sholeh; Erna Kumala Nurnawati (Jurnal PkM Pemberdayaan Masyarakat, 2023)
Game development is currently one of the opportunities in the creative industry. The game industry is one of the creative industries that is experiencing growth and has bright prospects in the future. At this time, games are not only as entertainment but can also be used as a means of learning. As an effort to introduce applications for developing games, the team from the AKPRIND Yogyakarta Institute of Science & Technology provided training on making game basics using the Scratch software. Scratch is software that can be used to introduce simple logic to participants. The process of developing game applications with Scratch does not use programs but is done by assembling blocks. The purpose of implementing community service includes providing insight to students at Tembarak Vocational School in learning the logic of developing game applications. Students can use Scratch software in the implementation of simple game development. The method used in carrying out activities is to use interviews, training and giving questionnaires as a process of evaluating activities. Questionnaires were conducted at the beginning and end of the training. Questionnaires at the beginning of the training were given with the aim of mapping students' knowledge in making game applications. The questionnaire at the end of the training was used to find out the benefits of the training results. The end result of the activity, students can get logic material for making games and students can make simple game applications with Scratch.